Analysis of Shallow Groundwater Quality for Domestic Use by the Community in Anggalomelai Village, Abeli District, Kendari City - Inggit Vidi Esa Wahyudi; La Ode Midi; La Ode Ahmad Nur Ramadhan; Muhammad Saleh Qadri (International journal of technology and education research, 2025)
Seawater intrusion is a groundwater problem in coastal areas because it can directly affect groundwater quality, resulting in an impact on the quality and quantity of the groundwater itself. Groundwater that was originally suitable for drinking has decreased in quality and is no longer suitable for daily use. This study aims to determine the quality status of shallow groundwater in Anggalomelai Village, Abeli District, Kendari City, using the Pollution Index Method as stipulated in the Decree of the Minister of Environment of the Republic of Indonesia Number 115 of 2003 concerning Guidelines for Determining Water Quality Status. Samples were taken at three different locations in Anggalomelai Village, then tested for parameters such as temperature, Total Dissolved Solids (TDS), Electrical Conductivity, Potential Hydrogen (pH), chloride, sodium, salinity, and E. coli. This research method refers to the quality standards set out in Government Regulation of the Republic of Indonesia Number 22 of 2021 concerning the Implementation of Environmental Protection and Management. The results showed that Sampling Point I was categorized as meetingquality standards with a Pollution Index value of 0.439 and a good status, while Sampling Point II was also categorized as meeting quality standards with a Pollution Index value of 0.283 and a good status. Sampling Point III falls into the category of meeting quality standards with a Pollution Index value of 0.597 with a good status . The conclusion of this study is that the quality status of shallow groundwater in Anggalomelai Village is classified as good.